Upaya Peningkatan Kualitas Hidangan Buffet Lunch di Hotel Aria Centra Surabaya - Siti Arifah Sabrina; Lilis Sulandari; Niken Purwidiani; Aisyah Nurin Kamiliya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The purpose of this final project is to describe efforts to improve the quality of buffet lunch dishes at the Aria Centra Hotel, Surabaya. This study uses theories from experts who study the improvement of the quality of buffet lunch dishes. The method used in this study is a qualitative method with a descriptive approach. This study uses interview and documentation techniques to support the qualitative approach. This study uses many data collection techniques used interviews and documentation. The focus of this study is to determine the improvement of the quality of breakfast menu dishes. The final results of this study indicate that the Aria Centra Hotel, Surabaya, has provided the quality of breakfast menu dishes according to the wishes of guests. The improvement in the quality of breakfast menu dishes is in accordance with the quality standards set by the chef team. The hotel industry in Surabaya is currently facing very competitive competition, so the Aria Centra Hotel, Surabaya, is required to continue to innovate and improve product quality to maintain guest loyalty. One of the superior services that is a meeting point for large guest interactions is the buffet lunch dish.